Justiça restaurativa no Brasil: limites, desafios e possibilidades no âmbito da justiça criminal - Silveira, Daniela Zini da (Universidade do Vale do Rio dos Sinos, 2020)
The objective of this research is to study the current state of justice restoration in Brazil, specifically the limits, challenges and possibilities for use and consolidation of this paradigm within the criminal justice system. A theoretical foundation was structured in three central parts and developed from of a bibliographical review of the international and national literature on the subject, with a focus on in empirical studies. As will be seen, the limits and legal possibilities, as well as such as operational and cultural challenges, do not prevent the use of justice restorative practices within the scope of Brazilian criminal justice, but hinder the entry and the use of this model as a basic and complementary response mechanism to any crime, in addition to directly affecting the sustainability of the programs to be long term.
Keywords: Justiça restaurativa; Sistema de justiça criminal; Conflitualidade penal; Reparação; Brasil; Restorative justice; Criminal justice system; Penal conflict; Reparation; Brazil